Human Cytomegalovirus (HCMV) UL82 Gene Product (pp71) Relieves hDaxx-Mediated Repression of HCMV Replication - Cantrell, Stacy R. (American Society for Microbiology, 2006)
This study examines the role of the cellular protein hDaxx in controlling human cytomegalovirus (HCMV) immediate-early (IE) gene expression and viral replication. Using permissive cell lines that either overexpress hDaxx or are depleted of hDaxx expression by the use of short hairpin RNA, we demonstrate that hDaxx functions as a repressor of HCMV IE gene expression and replication. In addition, we demonstrate that the impaired growth phenotype associated with the UL82 (pp71) deletion mutant is abolished when hDaxx knockdown cells are infected, suggesting that pp71 functions to relieve hDaxx-mediated repression during HCMV infection.